Titin antibodies in "seronegative" myasthenia gravis--A new role for an old antigen - Stergiou, C; Lazaridis, K; Zouvelou, V; Tzartos, J; Mantegazza, R; Antozzi, C; Andreetta, F; Evoli, A; Deymeer, F; Saruhan-Direskeneli, G; Durmus, H; Brenner, T; et al. (Journal of neuroimmunology, 2016)
Myasthenia gravis (MG) is an autoimmune disease caused by antibodies targeting the neuromuscular junction of skeletal muscles. Triple-seronegative MG (tSN-MG, without detectable AChR, MuSK and LRP4 antibodies), which accounts for ~10% of MG patients, presents a serious gap in MG diagnosis and complicates differential diagnosis of similar disorders. Several AChR antibody positive patients (AChR-MG) also have antibodies against titin, usually detected by ELISA. We have developed a very sensitive radioimmunoprecipitation assay (RIPA) for titin antibodies, by which many previously negative samples were found positive, including several from tSN-MG patients. The validity of the RIPA results was confirmed by western blots. Using this RIPA we screened 667 MG sera from 13 countries; as expected, AChR-MG patients had the highest frequency of titin antibodies (40.9%), while MuSK-MG and LRP4-MG patients were positive in 14.6% and 16.4% respectively. Most importantly, 13.4% (50/372) of the tSN-MG patients were also titin antibody positive. None of the 121 healthy controls or the 90 myopathy patients, and only 3.6% (7/193) of other neurological disease patients were positive. We thus propose that the present titin antibody RIPA is a useful tool for serological MG diagnosis of tSN patients.
Keywords: proteiny související s LDL-receptory; konektin; Radioimmunoprecipitation Assay; mezinárodní spolupráce; Receptors, Cholinergic; Diagnosis; radioimunoprecipitační analýza; receptory cholinergní; lidé; tyrosinkinasové receptory; International Cooperation; Radioimmunoprecipitation assay; mužské pohlaví; myasthenia gravis; Myasthenia gravis; Connectin; Seronegative; ženské pohlaví; ELISA; Humans; Myasthenia Gravis; Receptor Protein-Tyrosine Kinases; LDL-Receptor Related Proteins; Enzyme-Linked Immunosorbent Assay; Titin; Female; Autoantibodies; autoprotilátky; Male